ANALYSIS OF PEDAGOGICAL APPROACHES IN DEVELOPING COMMUNICATIVE COMPETENCE (American Journal of Pedagogical and Educational Research, 2023)
This article describes pedagogical strategies aimed at enhancing communicative competence, a crucial skill in language acquisition and use. The study investigates various instructional methods, techniques, and interventions employed in educational settings to develop learners' ability to effectively and contextually communicate in a target language. The article examines how engaging learners in real-life, communicative tasks enhances their language proficiency and encourages practical application of language skills in authentic situations. The article critically analyzes different assessment methods employed to measure communicative competence. It explores formative and summative assessment techniques that align with communicative language teaching principles, emphasizing the evaluation of learners' ability to use language meaningfully in real-world situations. This study holds significance for educators, curriculum developers, and policymakers seeking to optimize language instruction methodologies.